Perlindungan Konsumen Pada Cryptocurrency di Era Digital - Az Zahra Nashira Ryan; Aris Prio Agus Santoso; Giovania Madeira Do Carmo; Jonathan James Kurniawan; Zakkiya Muflih Gusma Putra (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The use of cryptocurrency assets in Indonesia is still prohibited as a means of payment but as an investment instrument it can be included as a commodity that can be traded on a term exchange as regulated in the regulation of Law No. 10 of 2011 concerning amendments to Law No. 32 of 1997. The positive impact of cryptocurrencies in consumer protection such as cryptocurrency financial access can provide access to the traditional banking system, thereby increasing financial inclusion. There are also negative impacts to consider in consumer protection: security risks associated with theft or hacking of cryptocurrency exchange platforms and digital wallets can threaten the security of consumer funds. This study aims to analyze about consumer protection of cryptocurrencies in the digital age. This research uses normative research methods and uses qualitative data types. The results of this study show that consumer protection in cryptocurrency in the digital era, among others, preventively, in cryptocurrency trading transactions as assets is also strengthened by the Regulation of the Commodity Futures Trading Supervisory Agency Number 9 of 2019 concerning Amendments to the Regulation of the Commodity Futures Trading Supervisory Agency Number 5 of 2019 concerning Textile Arrangements for the Implementation of the Physical Market of Cryptocurrency Assets on Futures Exchanges. Meanwhile, if repressively to protect what is given after a dispute arises in the form of sanctions, fines, imprisonment, and penalties imposed a dispute occurs, regulated in Article 22 of PerBappeti Number 5 of 2019 concerning Technical Provisions for the Implementation of the Physical Market of Cryptocurrency Assets on the Futures Exchange, that dispute resolution is carried out by deliberation to reach consensus if it does not reach consensus the parties can resolve through the Futures Trading Arbitration Agency Commodity (BAKTI) and the State Court as stated in the agreement between the parties. Bank Indonesia reaffirms the ban on the use of virtual currencies in cryptocurrency, both in the form of selling, buying, and trading with these currencies.